AB0081 Sub-Clinical Carotid Atherosclerosis in Patients with Gout. Preliminary Results. (10th June 2014) - Gutierrez, M.; Okano, T.; Salaffi, F.; Bruno, A.; Filippucci, E.; Grassi, W.
Abstract : Background: Gout is a disease characterized by and recurrent attacks of arthritis and hyperuricemia which has recently been considered an independent cardiovascular risk factor. Moreover, strong evidence supporting both proatherogenic and protrombotic characteristics of the inflammatory process in these patients have been published. Objectives: To determine the prevalence of increased cIMT, as sign of pre-clinical atherosclerosis, in patients with gout and asymptomatic hyperuricemia by an automated ultrasound (US) method based on radiofrequency. The secondary aim was to determine the reliability of the US in the assessment of cIMT. Methods: Eighty-four patients (48 with gout and 36 with hyperuricemia) were enrolled. Before the US cIMT assessment, all patients underwent a clinical examination aimed to record age, gender, disease, disease duration, smoking, sedentary, use of coffee, ischemic cardiopathy or peripheral arteriopathy, previous myocardial infarction or cerebrovascular events and familiar history for them in first relatives <50 years, comorbidities (including diabetes mellitus, type 1 or 2, systemic blood hypertension, dyslipidemia, renal insufficiency, obesity) waist circumference, and systemic blood pressure, current therapy. Moreover, erythrocyte sedimentation rate, C-reactive protein, total cholesterol, HDL-high-density lipoprotein, triglycerides, fasting serum glucose, serum creatinine, uricemia were recorded. US examinations of the IMT at both common carotids were performed by a rheumatologist expert in US, using a My Lab 70 XVG (Esaote SpA – Genoa- Italy) equipped by a linear probe (frequency, 4-13 MHz) and an automatic method (QIMT). This is based on the radio-frequency technology and provides in real-time a measure which is the average of six mean values obtained during six consecutive cardiac cycles. The inter- and intra-observer reproducibility in the US assessment of the IMT of both common carotids have been performed in 20 patients. For the IMT, the definition of Mannheim Carotid Intima-Media Thickness Consensus (2004–2006) was adopted. Results: A total of 168 common carotids were assessed. In 31 (64.5%) out of the 48 patients with gout and 22 (61.1%) out of the 36 patients with asymptomatic hyperuricemia, US detected an increased. The multiple regression analysis found a significant positive correlation between increased cIMT and both disease duration (p=0.0123) and age of the patients (p=0.0001). No significant correlation was found with the other clinical and laboratory parameters. Moreover no differences between US findings were found between gout and asymptomatic hyperuricemia. Inter-observer intraclass correlation coefficient (ICC) values were in a range from 0.74 to 0.82 whereas the ICC for the intra-observer was 0.63. Conclusions: Our results demonstrate that patients with gout and hyperuricemia without clinically evident cardiovascular disease have a high prevalence of atherosclerosis represented by the increased cIMT. Moreover the automated US radiofrequency technique of measurement of cIMT demonstrated to be a reliable and useful alternative to conventional approach to assess the cardiovascular risk in gout patients. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5666